Vegetation Characteristics of The Nesting Area of The Orange-Footed Scrubfowl (Megapodius reinwardt) In Tunak Mountain Natural Tourism Park Central Lombok District - Wardani, Heny; Yamin, M.; Khairuddin, Khairuddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Orange-footed scrubfowl (Megapodius reinwardt) is a protected species and needs to be preserved. They build mounds using leaves, twigs, plant litter and soil. The importance of plant vegetation around the Orange-footed scrubfowl nesting area while until this research was conducted no one had examined plant vegetation in Orange-footed scrubfowl nesting area became the background of this research. The data collection method of this research is by using the plotted method. Variables in this study include plant vegetation (tree diameter, number of individuals and tree species) and environmental data including temperature, humidity and light intensity. The results showed that the vegetation of Orange-footed scrubfowl nesting area in TWA Gunung Tunak has differences in species between one nest and another, but there are still many similar species. The diversity index shows that the vegetation around the nest is not diverse, ranging from 11-15 species with high dominance evenness. The species similarity index between inside the nest and outside the nest is high. This is also influenced by environmental factors that are not too different from one nest and another. Based on the results of the research that has been done, it is concluded that the vegetation of the gosong bird nesting area in the red foot of TWA Gunung Tunak has differences in species between one nest and another, but there are still many similar species.